Department of Agricultural and Resource Economics 1990-1992 publications - Cary, Nancy, author; Department of Agricultural and Resource Economics, Colorado State University, publisher (Colorado State University. Libraries, 1993)
The primary purpose of this publication listing is to help increase the accessibility to published research by the Department of Agricultural and Resource Economics (DARE) faculty, affiliates and graduate students to the general public and interested individuals.
March 1993
Compiled by Nancy Cary.
Keywords: Colorado State University. Department of Agricultural and Resource Economics -- Bibliography -- Catalogs; Agriculture -- Economic aspects -- Bibliography